(3CHh dgH hGeQCJg MeGdI GdMWH (B:s (3OQGSI ehVhYjI dShQI GdeSO (B/s - (3MeGO, CMeO Rcjs 1946- ((3OeTb (B- (3ShQjG (B:s (3OGQ Gdbde,s (3HjQhJ (B- (3dHfGf (B:s (3GdOGQ GdTGejI,s, 2001)
(3jJfGhd cJGH (B((3CHh dgH hGeQCJg MeGdI GdMWH OQGSI ehVhYjI dShQI GdeSO(B) (3hGdPj bGe HJCdjag O(B. (3CMeO Rcj MeGO, ehVhY (B((3OQGSGJ ESdGejI(B) (3GdcJGH jhVM dfG eDdag Cfg bO SLd GdbQBf LedI ef MhGOK GdYfa VO GdCfHjGA hGdeDefjf(B. (3hHjf GdPjf bGOhG MedI GdYfa VO GdfHj eMeO Udi Gddg Ydjg hSde hYeg (B"(3CHh dgH, YHO GdYRj Hf YHO GdeWdH(B"(3, hRhLg (B"(3Ce Lejd, CQhi HfJ MQH(B". (3dbO bQQG Cf jbaG aj GdNW GdChd eY RYeGA bQjT aj ecI, dMQH GdfHj Udi Gddg Ydjg hSde(B. (3hcQS CHh dgH cd WGbJg, hcd CSQJg heGdg ddVZW Ydi GdQShd Udi Gddg Ydjg hSde, hMQeGfg ef MQjI GdJYHjQ Yf QSGdJg, hMQeGfg ef YHGOI Gddg ceG jQi(B. (3hbO QCi GdeDda Cf jdbj fXQI YGeI Ydi HhGYK GdeYGQVI hGSJQGJjLjJgG aj ebGheI GdESdGe hLghOgG dEYGbI eSjQJg, hPdc (B"(3aj QCjg(B" (3jYjf Ydi age eYGdLI GdbQBf dgLeGJ GdeTQcjf(B. s
(3eLdO afj CHjV(B.s
Keywords: (3bQBfs -- (3JaSjQ ehVhYjs